Pengelolaan Sistem Penyediaan Air Minum (SPAM) Keceme dalam penanggulangan kekeringan: Studi kasus di Kabupaten Gunungkidul Yogyakarta - Roy Rahmanto; Bresca Merina (Prosiding Seminar Nasional Ilmu Manajemen Kewirausahaan dan Bisnis, 2025)
This study aims to describe the management of the Keceme Drinking Water Supply System SPAM as an effort to overcome drought in Waru Hamlet, Girisekar Village, Panggang District, Gunungkidul Regency, Special Region of Yogyakarta. The drought problem in the area has been going on for a long time, thus demanding a sustainable solution to meet the community's clean water needs. This study uses a qualitative approach with data collection techniques through observation, in-depth interviews with SPAM managers and the community, and documentation. Data analysis was carried out with reference to George R. Terry's management theory which includes four management functions, namely planning, organizing, actuating, and controlling. The results show that the existence of the Keceme SPAM greatly helps the community in obtaining access to clean water, although various obstacles still exist. The main obstacles include planning that is mostly not documented in writing, limited number and capacity of human resources in management, technical problems in the form of lime deposits that disrupt water flow, and high operational and maintenance costs of the network. However, the existence of social capital in the form of a spirit of mutual cooperation among the community, as well as policy support and facilities from the village government, are important factors driving the sustainability of SPAM management. This research is expected to provide practical contributions as a reference for other regions facing similar challenges, particularly in optimizing the use of local water sources as a sustainable drought mitigation strategy.